Integrated Marketing Communication Program Formulationfor Green Tea Chocolat Arafa Teausing Benchmarking Approach - Alan Arif Dharmasaputra; Yati Rohayati; Atya Nur Aisha (eProceedings of Engineering, 2015)
Abstract: Arafa Tea is a Small and Medium Enterprises (SME’s) business that produces products based green tea. One of the flagship products are Green Tea Tea Arafa Chocobar (GTC), which contribute greatly to the income of Arafa Tea. But due to the marketing area is still narrow which are Ciburial and Lembang and ways of marketing communication that is used only uses activities such as exhibitions, Arafa Tea has the desire to expand the market to consumers that lives in the City of Bandung. This study aims to formulate a marketing communications program that can be implemented by Arafa Tea in marketing the product GTC. This research was conducted using the method of benchmarking against similar business and direct competitors to find the best practice as a basis for formulating marketing communications program for Arafa Tea. Parameters will be benchmark are media and content of communication used, stretegi marketing, marketing communications program. The recommended program will be matched with the capabilities and resources owned SMEs Arafa Tea. Based on the results of benchmarking has been done Arafa Tea has the potential to market their products to the city of Bandung. For that Arafa Tea need to formulate a new communications program that can be applied ie packaging designed by the designer, the use of internet media, namely Facebook as a medium of communication and reseller programs. Keywords: Marketing Communications Program, Benchmarking Analysis